Dewaterability of thermal conditioned sewage sludge after anaerobic stabilization = Efektywność odwadniania termicznie kondycjonowanych osadów ściekowych poddanych stabilizacji beztlenowej - Małkowski, Mariusz; Wolski, Paweł; Wolny, Lidia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Thermal pretreatment of sewage sludge influences the improvement of biochemical decomposition of sludge in the anaerobic stabilization process. At the same time the ratio of fermentation impacts on the effectiveness of sludge dewatering. The aim of investigation was the evaluation of thermal conditioned excess sludge dewaterability after anaerobic stabilization process.
Keywords: osady ściekowe; kondycjonowanie termiczne; stabilizacja beztlenowa; odwadnianie; sewage sludge; thermal conditioning; anaerobic stabilization; dewatering